Effectiveness of topical gabapentin in the treatment of vulvodynia: a narrative synthesis - Ergisi, Mehmet; Law, Alexander; Chaudhari, Nishant; Tsatsari, Stefania; Lawson, Kim; Jenner, Christopher (Frontiers in Pain Research, 2023)
Vulvodynia is a leading cause of dyspareunia in premenopausal women, causing considerable morbidity and sexual dysfunction. A multimodal approach is used to treat vulvodynia. Alongside psychosocial interventions and physiotherapy, pharmacological treatment such as oral gabapentin are used in the treatment of vulvodynia. Topical formulations of gabapentin have shown promise in animal models and case reports investigating its use in other pain conditions. The topical route also avoids the systemic complications of gabapentin such as somnolence, dizziness, and peripheral edema. This study aimed to perform a narrative synthesis of studies investigating the use of topical gabapentin in the treatment of vulvodynia. The primary outcome was a change in pain score following treatment with topical gabapentin. A broad literature search was performed, which identified four studies for inclusion. The included studies reported improved pain measures following treatment; however, conclusions cannot be made due to methodological heterogeneity and inherent limitations. These include lack of control arms, small sample sizes, lack of patient randomization, and use of combination treatments. Due to the paucity of evidence, this review supports the future implementation of double-blind randomized controlled trials to further investigate the efficacy of topical gabapentin in the treatment of vulvodynia.